Blood Pressure, Smoking, and the Incidence of Lung Cancer in Hypertensive Men in North Karelia, Finland - Lindgren, Annamarja; Pukkala, Eero; Nissinen, Aulikki; Tuomilehto, Jaakko (American Journal of Epidemiology, 2003)
Few studies have suggested that elevated blood pressure might be associated with increased risk of lung cancer and that this association might vary according to smoking status. The aim of this study was to assess the effect of blood pressure and its possible interaction with smoking on lung cancer incidence in hypertensive patients. Lung cancer incidence was determined for 7,908 men enrolled in the hypertension register of the North Karelia Project between 1972 and 1988 by record linkage to the nationwide Finnish Cancer Registry. In a Cox regression model, both systolic and diastolic blood pressures were significant predictors of lung cancer, with a 10% increase in risk per 10-mmHg increment in blood pressure. In smokers, the age-adjusted hazard ratio associated with a 10-mmHg increment in diastolic blood pressure was 1.17 (95% confidence interval: 1.05, 1.29), and in nonsmokers it was 0.98 (95% confidence interval: 0.80, 1.16). For systolic blood pressure, these hazard ratios were 1.11 (95% confidence interval: 1.05, 1.17) for smokers and 1.04 (95% confidence interval: 0.95, 1.14) for nonsmokers. These findings suggest that high blood pressure levels are associated with increased risk of lung cancer in smoking, hypertensive men.